Effects of SGLT2 inhibitors on patients with diabetic kidney disease: A preliminary study on the basis of podocyturia. Issue 4 (28th February 2022) - Durcan, Emre; Ozkan, Serbay; Saygi, Halil Ibrahim; Dincer, Mevlut Tamer; Korkmaz, Ozge Polat; Sahin, Serdar; Karaca, Cebrail; Sulu, Cem; Bakir, Alev; Ozkaya, Hande Mefkure; Trabulus, Sinan; Guzel, Elif; et al.
Abstract: Background: The aim of this study was to investigate the effects of sodium glucose cotransporter 2 inhibitors (SGLT2i) on the glomerulus through the evaluation of podocyturia in patients with diabetic kidney disease (DKD). Methods: The study population was composed of 40 male patients with type 2 diabetes mellitus; 22 of them received SGLT2i (SGLT2i group), and the others who did not were the control. The DKD‐related parameters of patients were monitored before SGLT2i initiation, and then in the third and sixth month of the follow‐up period. Patients' demographic, clinical, laboratory, and follow‐up data were obtained from medical charts. Microalbuminuria was measured in 24‐h urine. The number of podocytes in the urine was determined by immunocytochemical staining of two different markers, namely podocalyxin (podx) and synaptopodin (synpo). Concentrations of urine stromal cell‐derived factor 1a and vascular endothelial growth factor cytokines were quantified with an enzyme‐linked immunosorbent assay kit. Results: At the end of the follow‐up period, decreases in glycosylated hemoglobin, glucose, systolic and diastolic blood pressure, uric acid level, and microalbuminuria, and improvement in body mass index level and weight loss were significant for the SGLT2i group. On the other hand, there was no significant difference in terms of these parameters in the control group. The excretion of synaptopodin‐positive (synpo + ) and podocalyxin‐positive (podx + ) cells was significantly reduced at the end of the follow‐up period for the SGLT2i group, while there was no significant change for the control. Conclusions: At the end of the follow‐up period, male patients receiving SGLT2i had better DKD‐related parameters and podocyturia levels compared to baseline and the control group. Our data support the notion that SGLT2i might have structural benefits for glomerular health. Abstract : Highlights Diabetic kidney disease is a progressive disease with the pathology of glomerular damage and loss of podocytes. Sodium glucose cotransporter 2 inhibitors (SGLT2i) can be expected to decrease the amount of podocyte excretion. Male patients receiving SGLT2i have better diabetic kidney disease‐related parameters and podocyturia levels. 摘要: 背景: 本研究旨在通过对糖尿病肾病(DKD)患者尿足细胞的评估, 探讨钠葡萄糖共转运体2抑制剂(SGLT2i)对肾小球的影响。 方法: 研究对象为40例男性2型糖尿病患者, 其中22例接受SGLT2i治疗(SGLT2i组), 另22例未接受SGLT2i治疗作为对照组。在SGLT2i治疗前、随访期第3个月和第6个月监测患者的DKD相关参数。从病历中获得患者的人口学、临床、实验室和随访数据。24小时中测定尿微量白蛋白。通过两种不同的标记物, 即Podocalyxin (podx)和Synaptopodin (synpo)的免疫细胞化学染色来确定尿足细胞的数量。用酶联免疫吸附分析试剂盒检测尿基质细胞衍生因子1a和血管内皮生长因子细胞因子的浓度。 结果: 在随访结束时, SGLT2i组糖化血红蛋白、血糖、收缩压、舒张压、尿酸水平、微量白蛋白尿均显著下降, 体重指数和体重减轻明显改善。另一方面, 对照组的这些参数没有显著差异。SGLT2i组synpo+和podx+的排泄量在随访期结束时显著减少, 而对照组无明显变化。 结论: 在随访期结束时, 接受SGLT2i治疗的男性患者与基线和对照组相比, 有更好的DKD相关参数和尿足细胞水平。我们的数据支持SGLT2i对肾小球健康有结构性益处的观点。